SENSITIVITAS DAN SPESIFISITAS DIAGNOSIS TB PADA KASUS TB PARU TAHUN 2019 - Mardan Ginting; Nita Andriani Lubis; Gabriella Septiani Nasution; Lestari Rahmah (Poltekkes Kemenkes Medan, 2022)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium Tuberculosis which can attack various organs, especially the lungs. However, before treatment, the diagnosis needs to be made through laboratory tests with the right method with good sensitivity and specificity The purpose of this study was to determine the level of sensitivity and specificity of TB diagnoses. The research method is a descriptive analytic survey research with cross sectional design research design research was conducted from May to October 2019. The place of research was conducted at Pancur Batu Health Center Deli Serdang for taking sputum specimens and blood samples of TB suspect patients. The number of samples in this study were 33 people. The results obtained by the sensitivity and specificity of BTA by 75% and 88.9%. The results obtained sensitivity and specificity of GeneXpert of 95.8% and 100%. The results obtained sensitivity and specificity of Tuberculosis Immunocromatography (ICT) of 28% and 100%. The research results obtained sensitivity and specificity of Interferon Gamma Release Assay (IGRA) of 88% and 100%. BTA is suitable for use, the GeneXpert method is used for the TB RO program and the MGIT Gold Standard for MDR TB.